The Meningkatkan Kemampuan Implementasi Merdeka Belajar Melalui Seminar Online Bagi Guru dan Kepala Sekolah - Sophia Tri Satyawati; Yari Dwikurnaningsih; Bambang Ismanto; Ade Iriani; Marinu Waruwu; Wasitohadi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The essence of independent learning is to explore the greatest potential of teachers and students to innovate and improve the quality of learning independently. However, the facts show that not a few teachers and principals do not fully understand the essence of free learning and how to implement it independently in their respective schools. This community service activity aims to improve the ability to implement free learning policies for teachers and principals of PAUD, Kindergarten, Elementary, Middle and High Schools in Semarang Regency, Salatiga City, Brebes Regency and Blora Regency. The form of activity is an online seminar using zoom media with lecture and discussion methods carried out in two (2) stages. The level of achievement of the attendance of the first stage participants was 131 (87.33%) in the GOOD category. The attendance of the second stage participants was 326 (108.66%) in the VERY GOOD category. The level of perception of the participants showed: 1) The material presented reached 91.05% in the VERY GOOD category; 2) The performance of the speakers reached 88.16% in the GOOD category; 3) Participants' satisfaction reached 87.03% in the GOOD category. The level of understanding of the essence and implementation of independent learning is shown in the description of positive responses about the benefits of the seminars that are attended and constructive criticism and suggestions from participants on the implementation of online seminars.